Fatores associados à tomada de decisão clínica no manejo de dentes tratados endodonticamente: comparação entre especialistas e não-especialistas - Lena, Isabella Marian (2021)
The present study aimed to evaluate the influence of factors related to the professional and the tooth (clinical and radiographic data) and the impact of radiographic characteristics, when assessed individually or together, on the clinical decision-making process of specialists or non-specialists in endodontics regarding the management of endodontically treated teeth. The sample comprised 28 participants, 14 endodontists and 14 general dentists (non-endodontists). Participants evaluated 30 clinical cases containing endodontically treated teeth, at four different time points, with one-month intervals, by electronic questionnaires: T1, evaluation of edited digital periapical radiographs (the periapex was covered), allowing only the visualization of the tooth and the classification of root filling quality; T2, evaluation of edited digital periapical radiographs (the tooth was covered), allowing only the visualization of the periapical area and the classification of periapical status; T3, analysis of the complete radiograph (without edition); T4, analysis of the complete radiograph, associated with patient’s clinical data. At all time points, participants evaluated the root filling quality and/or periapical status, and chose the best treatment option for that tooth: no intervention/wait and see, endodontic retreatment, apical surgery, endodontic retreatment + apical surgery, or extraction. The confidence level to define the diagnosis and the treatment, and the need for cone-beam computed tomography (CBCT) were also evaluated. A Multivariable logistic regression model, having as outcome the treatment option at T4 (wait and see or reintervention), was used to evaluate the impact of participants’ personal characteristics, and radiographic and clinical variables of the tooth at the different time points (T1 to T4) in the decision to retreat or not a tooth. Data regarding the confidence level were analyzed by the Man-Whitney, Friedman and Wilcoxon tests. Regarding the request of CBCT, the data were compared with Qui-square, Q Cochran and McNemar tests (α=5%). The results demonstrated that the presence of signs and symptoms was the variable that most impacted the decision to retreat a tooth (OR: 9.58; CI 95%: 6.24-14.70). However, root filling quality at T4 (OR: 5.34; CI 95%: 3.51-8.12) and periapical status at T2 (OR: 1.66; CI 95%: 1.07-2.57) and T4 (OR: 4.27 CI 95%: 2.54-7.17) had also influenced the decision-making process. Regarding participants’ personal characteristics, gender (female) and experience level (endodontists) were significantly related to reintervention. In general, clinicians with special training in endodontics were more confident and requested more CBCT as a complementary exam (P<0.05) than non-specialists. In conclusion, gender, experience level, clinical signs and symptoms, root filling quality (T4) and periapical status (T2 and T4) influenced the decision-making process. Also, the confidence level in diagnosis and treatment options and the request of CBCT were higher in the specialist group compared to non-specialists.